A classe operária vai à universidade: um estudo sobre a dimensão qualitativa da participação sindical de trabalhadores graduandos em Direito da Universidade Federal de Minas Gerais (UFMG) - Rosa Juliana Cavalcante da Costa (2018)
The study is devoted to the analysis of the relations between workers and Unions, under neoliberal contextualization in Brazil, especially since the 1990s. The perception of the class about its representative entity, the role it has to play and the affinities and dissonances between category expectations and the strategies of their leaders: the central objective is to analyze the distance between workers and class entities, in order to assess the validity of the thesis on the crisis of unionism. It also seeks to understand the influence of the Universidade Federal de Minas Gerais and, particularly, of legal education, the construction of the perception of the workforce and the formation of a political consciousness about Labor Law, collective action and the material reality of the workers, as well as to study the answers obtained under the prism of the right put, in its gaps, contradictions and possibilities of resistance. Methodologically, the research reconciled a bibliographical study on the mutations introduced by the system of flexible accumulation to the central elements of the study, workers-Unions-University, with field research, through the application of semistructured questionnaires to undergraduate students of the Law course of the Universidade Federal de Minas Gerais, concluding the last school term. The data obtained indicated that the separation between workers and representative entities is not limited to the quantitative aspect, but is also felt among affiliates, and can be attributed to a more restrictive contractualist understanding that associates the class organizations to the limits of the employment relationship. It was also observed that the Academy has a small contribution to the approach of undergraduate workers of the collective cause and of the Union, offering limited space for the issue and reproducing the silences and antinomies that the Law itself maintains in relation to the protective labor framework.